The Politics of the Sustainable Development Goals - Bexell, Magdalena (Routledge Studies in Sustainable Development, 2021)
This book draws attention to political aspects of sustainable development goal-setting, exploring the Sustainable Development Goals (SDGs) at the global-national nexus during their first five years.